수치해석을 활용한 ONR Tumblehome의 유효반류비 추정에 관한 연구 - 이준희(Jun-Hee Lee); 서성부(Sung-Bu Suh) (大韓造船學會 論文集, 2019)
This paper carried out numerical analysis for estimating the propulsion performance of the model scale ONRT benchmark model of'Tokyo 2015 a workshop on CFD'. The method reflecting the scale effect of ITTC'78 method and form factor were used to compare the estimates of the effective wake ratio of full-scale. The numerical calculation was performed with Siemens's Star-CCM+, compared with IIHR model tests and the numerical analysis results of other research institutes, showing good agreement. In the case of an open stern and twin skeg ship, the validity of the ITTC'78 method can be confirmed by assuming that the effective wake ratio estimated from the numerical analysis results of model scale is similar to the effective wake ratio of full-scale.